AI-Based Platform for Accessing Level-Appropriate Texts on Specific Topics: The LATILL Project. - Mudra, Olena (CPN Publishing Group., 2025)
In modern language education, the effective development of reading skills largely depends on selecting texts that match learners’ proficiency levels. The LATILL project, a pioneering initiative, addresses this challenge by leveraging AI-based tools to facilitate the search for level-appropriate, topic-specific texts for teaching German as a foreign (DaF) or second language (DaZ). This paper discusses the objectives, methodology, and innovative contributions of LATILL, highlighting its potential impact on language education.
Keywords: LATILL; digital platform; integrating AI; authentic texts; education